Factors influencing customer trust in salespersons in a developing country - Andaleeb, Syed Saad; Anwar, Syed Ferhat (© 1996 American Marketing Association, 2016)
This article was published in the Journal of International Marketing [© 1996 American Marketing Association] and the definite version is available at : http://www.jstor.org/stable/25048670